Implementasi Media Pembelajaran Biologi Berbasis Budaya Lokal Sebagai Upaya Penguatan Kearifan Lokal Dalam Pembelajaran - Gebyta Yani Ndaha Gebyta Yani Ndaha; Hairen Br Kaban Hairen Br Kaban; Estera; Lamtiurma Lumbantoruan; Putri Patricia Pandiangan; Rizal Mukra; Widya Arwita (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
This study aims to implement biology learning media based on local culture as an effort to strengthen local wisdom in the learning process. The research was conducted at SMA Negeri 11 Medan using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation during biology learning activities that integrated local cultural elements as media and learning contexts. The results show that the application of culture-based learning media increased students’ learning interest, reinforced local wisdom values, and made biology learning more contextual and meaningful. Furthermore, students demonstrated improved critical thinking skills and appreciation of their surrounding cultural environment. This implementation has the potential to serve as an alternative model for biology learning that aligns with regional characteristics and promotes the preservation of local values. Keywords: biology, contextual learning, learning media, local culture, local wisdom